Answer:
(5x-1)(3x+2)
(if you don't want to do all of this you can use
Explanation:
((3•5x2) + 7x) - 2
Factoring 15x2+7x-2
The first term is, 15x2 its coefficient is 15 .
The middle term is, +7x its coefficient is 7 .
The last term, "the constant", is -2
Step-1 : Multiply the coefficient of the first term by the constant 15 • -2 = -30
Step-2 : Find two factors of -30 whose sum equals the coefficient of the middle term, which is 7 .
-30 + 1 = -29
-15 + 2 = -13
-10 + 3 = -7
-6 + 5 = -1
-5 + 6 = 1
-3 + 10 = 7 That's it
Step-3 : Rewrite the polynomial splitting the middle term using the two factors found in step 2 above, -3 and 10
15x2 - 3x + 10x - 2
Step-4 : Add up the first 2 terms, pulling out like factors :
3x • (5x-1)
Add up the last 2 terms, pulling out common factors :
2 • (5x-1)
Step-5 : Add up the four terms of step 4 :
(3x+2) • (5x-1)
Which is the desired factorization